Critical Comparison Between Modified Monier-Williams and Electrochemical Methods to Determine Sulfite in Aqueous Solutions - Aguirre-Quintana, M; Aguirre-Quintana, M; Velez-Cifuentes, J; Arce-Escobar, R; Arce-Escobar, R (2012)
Sin Editorial Disponible